An experimental investigation on the settling velocity and drag coefficient of micrometer-sized natural, IG-110, NG-CT-10 and A3-3 graphite particles. (June 2021) - Fang, Zhu; Zhang, Yiyang; Zhao, Shumiao; Li, Xiaowei; Wu, Xinxin; Sun, Libin
Abstract: Micrometer-sized graphite particles are widely found in nature and industry. Particularly, the graphite dust is an important problem for the pebble-bed high temperature gas-cooled reactor (HTGR), regarding the coupling with the fission products (FPs). Due to the highly irregular disk-like shape, a great gap still exists for understanding the transport-related behaviors of real graphite particles, including the settling velocity and drag coefficient. To address this issue, we present an experimental investigation on the free settling of micrometer-sized natural, IG-110, NG-CT-10 and A3-3 graphite particles. The steady settling process is filmed using a high-speed camera together with a microscope. Both the terminal settling velocity and the drag coefficient are measured. In the Stokes region, although the shape is highly irregular and diverse, the statistical results show that the drag coefficient still follows the form of Stokes law and scales inversely proportional to the particle Reynolds number. Adopting the Stokes form and modifying the coefficient, a new correlation is proposed for the drag coefficient. The fitted value is 30.7 ± 10.2 for natural graphite, 26.2 ± 7.5 for IG-110, 28.1 ± 8.4 for NG-CT-10 and 32.7 ± 8.3 for A3-3 particles, which are larger than 24 of the classical spherical Stokes solution. In a wide range of particle Reynolds number from 10 −4 to 3, the Bagheri and Bonadonna's correlation well represents the drag coefficient of graphite particles. The results of this work can be easily incorporated into Eulerian-Lagrangian simulations and aerosol models in system analysis codes, and helps to improve the understanding and modelling of irregular disk-like graphite particles. Highlights: Settling velocity and drag coefficient of micrometer-sized graphite particles are measured. Experimental particles include IG-110, NG-CT-10, and A3-3 nuclear graphite. Drag coefficient still follows Stokes law but with a different coefficient other than 24. New correlation for drag coefficient covers a wide range of Re p from 10 −4 to 0.4.